2014
DOI: 10.1155/2014/842917
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence and Pattern of Superficial Fungal Infections among School Children in Ile-Ife, South-Western Nigeria

Abstract: Fungal infections of the skin and nails are common global problems with attendant morbidity among affected individuals. Children are mostly affected due to predisposing factors such as overcrowding and low socioeconomic factors. The aim of this study was to determine the prevalence and the clinical patterns of superficial fungal infections among primary school children in Ile-Ife. A multistage sampling was conducted to select eight hundred pupils from ten primary schools in Ile-Ife. Data on epidemiological cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

13
78
4
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(96 citation statements)
references
References 20 publications
13
78
4
1
Order By: Relevance
“…In Nigeria, the ratio was reported to be 0.06% and in the trial by Ertas et al involving 51 cases, the ratio was reported to be 7.8% (9,16). In this study, we found t. corporis at a ratio of 26% in 136 children in total with 5 occurring on the face.…”
Section: Discussionsupporting
confidence: 45%
“…In Nigeria, the ratio was reported to be 0.06% and in the trial by Ertas et al involving 51 cases, the ratio was reported to be 7.8% (9,16). In this study, we found t. corporis at a ratio of 26% in 136 children in total with 5 occurring on the face.…”
Section: Discussionsupporting
confidence: 45%
“…Scalp ringworm was the commonest form of the disease encountered in children, which is in agreement with reports from other parts of the world [16]. This is probably because infancy and childhood predispose to this form of mycoses, as adult sebum is believed to contain certain fungistatic fatty acids [17].…”
Section: Discussionsupporting
confidence: 85%
“…However, Trichophyton rubrum is the most frequently isolated species. 1,2,4,11,13,14,17,27,[33][34][35]39,40,42,46,48,53,55 Also, in our patients Trichophyton rubrum was the most frequently involved dermatophyte (6 out of 18 patients), followed by Microsporum canis (4 patients). Other dermatophytes responsible for tinea manuum are Epidermophyton floccosum, 20 Microsporum canis, 45 Trichophyton interdigitale, 37,47,50 Trichophyton mentagrophytes, 23,44 Trichophyton tonsurans, 3,28 Trichophyton verrucosum 21,36 and Trichophyton violaceum.…”
Section: Discussionsupporting
confidence: 53%
“…Epidemiological studies on tinea manuum have been carried out in several countries: Denmark, 3 Poland, 8,34 Greece, 22,27,48 Libya, 13,14 Senegal, 51 Nigeria, 40 Syria, 52 Iran, 9,16,20,23,30,32,36,37,44,45,47,50,53,55 China, 24,35,46 Japan 33,42 and the United States. 1,2 Incidence of tinea manuum is extremely changeable: 4.4% of all superficial mycoses in Poland, 8 .5% in Greece, 27 .6% in Libya, 13,14 in Syria, 52 from 4.2 37 to 16.4% 50 in Iran, 13.5% in China.…”
Section: Discussionmentioning
confidence: 99%